Production and Characterization of the New Thermoplastic Polymer by Linseed Oil and Glycerol Following Green Chemistry Principles - Alarcon, R. T. [UNESP]; Holanda, B. B. C. [UNESP]; Oliveira, A. R. [UNESP]; Magdalena, A. G. [UNESP]; Bannach, G. [UNESP] (Brazilian Chemical Soc, 2017)
This paper presents the synthesis of polymer from biomass (linseed oil and glycerol) aiming at green chemistry, environmental sustainability with low cost. The polymer has thermoplastic characteristics. The thermal characterization were performed by thermoanalytical techniques: Simultaneous Thermogravimetric-Differential Thermal Analysis and Derivative Thermogravimetric (TG-DTA/DTG), Differential Scanning Calorimetry (DSC). To complete the thermoanalytical data, further studies were used such as Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), Xray diffraction by the powder method (XRPD), inherent viscosity, density and Solvent Resistivity.
Keywords: Biomass; Thermoplastic Polymer; Green Chemistry